Radiotherapy plus EGFR inhibitors: synergistic modalities. Issue 1 (December 2017) - Bossi, Paolo; Platini, Francesca
Abstract Locally advanced (stage III or IV) squamous cell carcinoma of the head and neck (SCCHN) often requires multimodal treatment, consisting of a combination of surgery, radiation, and/or systemic therapy, namely chemotherapy or targeted agents. The expression of the epidermal growth factor receptor (EGFR) has been detected in more than 90% of all cases of SCCHN and has been correlated with decreased survival rates, resistance to radiotherapy, loco-regional treatment failure, and increased rates of distant metastases. This paper discusses several strategies aimed at targeting EGFR in combination with radiation. Until now, cetuximab, an anti-EGFR monoclonal antibody, is the only targeted agent that has been shown to improve overall survival in combination with radiation therapy. However, considering that there are multiple mechanisms of primary and acquired resistance to EGFR inhibitors, we focused on dissecting molecular pathways of EGFR inhibition to find alternative or complementary strategies for increasing tumour responsiveness. We suggest that the combination of treatments targeting the EGFR pathway and drugs aimed at increasing immune responses represent a promising approach that deserves to be further explored.